Penguatan Nilai-Nilai Moderasi Beragama Bagi Generasi Z di Desa Sokaraja Lor - Muhammad Muzadi Rizki (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Sokaraja Lor village is a very diverse village (differences between religions, differences between internal religions, etc.) and is still low on media literacy. Therefore, it needs to be managed properly so that the radicalism virus cannot enter the community. KKN-MB is one of the programs for students in carrying out their service in the community. Students are required to provide assistance, training, and strengthening which is expected to be internalized by the entire community in carrying out all their activities in accordance with the values ​​of religious moderation (fair and balanced, cooperation, grace, tolerance and benefit). The targets carried out by the devotees are all people in the community but focus on mentoring for Generation Z. The method used is Participatory Action Research (PAR), and the duration of service activities is 45 days. The conclusion from the implementation of the dedication of efforts in eradicating radicalism for generation Z is first, the religious moderation webinar activity. This activity is to always learn to open an inclusive mind. Second, clean the grave of Suroan, and finally, TPQ activities include the implementation of the Koran and art performances for pious children.